2022
DOI: 10.1038/s41467-022-32577-6
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the human NK cell NKR-P1:LLT1 receptor:ligand complex reveals clustering in the immune synapse

Abstract: Signaling by the human C-type lectin-like receptor, natural killer (NK) cell inhibitory receptor NKR-P1, has a critical role in many immune-related diseases and cancer. C-type lectin-like receptors have weak affinities to their ligands; therefore, setting up a comprehensive model of NKR-P1-LLT1 interactions that considers the natural state of the receptor on the cell surface is necessary to understand its functions. Here we report the crystal structures of the NKR-P1 and NKR-P1:LLT1 complexes, which provides e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 84 publications
1
2
0
1
Order By: Relevance
“…On the other hand, transfection of LLT1 into NK target cells protects them from human NK cell cytotoxicity in a CD161-dependent manner ( 22 ), while NK cell treatment with soluble LLT1 protein leads to inhibition of NK cell cytotoxicity towards target cells, both in our study and recently published study of Blaha et al. ( 32 ). In agreement with other reports ( 21 ) indicating that CD161 expression on NK cells marks a pro-inflammatory NK cell subset, we observed that CD161 + NK cells more effectively limit SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 73%
“…On the other hand, transfection of LLT1 into NK target cells protects them from human NK cell cytotoxicity in a CD161-dependent manner ( 22 ), while NK cell treatment with soluble LLT1 protein leads to inhibition of NK cell cytotoxicity towards target cells, both in our study and recently published study of Blaha et al. ( 32 ). In agreement with other reports ( 21 ) indicating that CD161 expression on NK cells marks a pro-inflammatory NK cell subset, we observed that CD161 + NK cells more effectively limit SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 73%
“…8c ). The genes of the C-type lectin superfamily are highly expressed in NK cells and may be involved in the regulation of the activity of NK cells 40 . The decreased activity of the CLEC pathway in LN + AM might result in a decrease in NK and NKT cells.…”
Section: Resultsmentioning
confidence: 99%
“…IFN-γ вырабатывают: естественные киллеры (NK), клетки естественных Т-киллеров, макрофаги, дендритные клетки (ДК), CD8 + и CD4 + T-клетки при адаптивном иммунном ответе и В-лимфоциты (таблица) [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: клетки-продуценты интерферона гаммаunclassified